2009
DOI: 10.1098/rspb.2009.0141
|View full text |Cite
|
Sign up to set email alerts
|

Spectacular morphological novelty in a miniature cyprinid fish, Danionella dracula n. sp.

Abstract: Danionella dracula is a new species of sexually dimorphic, miniature and highly developmentally truncated cyprinid fish. Compared with its close relative, the zebrafish Danio rerio , it lacks 44 bones or parts thereof and represents one of the most developmentally truncated vertebrates. Absence of the majority of bones appears to be due to developmental truncation via terminal deletion. In contrast to these larval-like features, D. dracula also shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
116
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 26 publications
2
116
1
1
Order By: Relevance
“…This is the first complete mitochondrial genome sequence from genus Pectenocypris. The phylogenetic tree (Figure 1) suggested that Rasbora is not monophyletic in relation to genera Trigonostigma, Pectenocypris, and Boraras, which is in agreement with earlier molecular studies (R€ uber et al 2007;Britz et al 2009;Tang et al 2010). It was also suggested that contrary to the earlier work (e.g.…”
contrasting
confidence: 55%
“…This is the first complete mitochondrial genome sequence from genus Pectenocypris. The phylogenetic tree (Figure 1) suggested that Rasbora is not monophyletic in relation to genera Trigonostigma, Pectenocypris, and Boraras, which is in agreement with earlier molecular studies (R€ uber et al 2007;Britz et al 2009;Tang et al 2010). It was also suggested that contrary to the earlier work (e.g.…”
contrasting
confidence: 55%
“…These genetic changes in multiple pathways likely comprise the constraint that has rendered loss of these teeth irreversible. Such a constraint would explain the appearance of bony projections from the jaw in D. dracula (18) and several lineages of fish-eating cypriniforms (12) in response to likely selection for the function provided by true oral teeth.…”
Section: Eda Overexpression Does Not Restore Teeth To the Mouth Of Thmentioning
confidence: 99%
“…These piscivorous cypriniforms have been suggested to be less-efficient predators than other taxa with more extensive dentition (11,16,17). In addition, the cypriniform species Danionella dracula has evolved dramatic fangs, not by regaining oral teeth but by sculpting the shape of bones of the jaw margin (18).…”
mentioning
confidence: 99%
“…The kinethmoid is a cypriniform synapomorphy and is ubiquitous across this clade of nearly 3500 species (Simons and Gidmark, 2010), with the exception of one highly miniaturized species (Britz et al, 2009). The kinethmoid is an unpaired, midline sesamoid bone or cartilage that develops within the intermaxillary ligament (Staab and Hernandez, 2010).…”
Section: Introductionmentioning
confidence: 99%